A randomised control trial for the restoration of functional ability in patients post total knee arthroplasty: Eccentric versus concentric cycling ergometry - Silal, Sandhya Prakash (Department of Health and Rehabilitation Sciences, 2020)
Introduction: While the total knee arthroplasty procedure improves joint-specific outcomes, including pain and range of movement, functional deficits post-surgery has been noted. Movement abnormalities and quadriceps weakness of the operated limb, as well as a decrease in strength on the non-operated have been widely reported. Recovery of strength and function to normal levels is also rare, thereby predisposing patients to future disability with increasing age. The purpose of this study was to determine the effects of an eight-week eccentric cycling ergometry exercise intervention versus a concentric cycling ergometry exercise intervention in total knee arthroplasty recipients three to nine months post-surgery. This study aimed to a) investigate the change in joint kinetics, kinematics and muscle activity during the phases of gait, between the eccentric and concentric groups over time and b) To determine if an eccentric cycling exercise intervention produces greater improvements in knee function when compared to concentric cycling exercise. Methods: Eighteen participants, three to nine months post total knee arthroplasty were recruited and randomly assigned to either an eccentric or concentric cycling exercise intervention group. Participants performed three exercise sessions weekly over a progressive eight-week period on the Grucox Isokinetic Ergometer. Walking gait analyses and functional outcomes, as measured by the six-minute walk test and validated knee scores (Knee Injury and Osteoarthritis Outcome Score, SF-36 Health Survey and Tegner Activity Scale) were recorded pre- and post-intervention. Results: The concentric group knee flexion range of movement increased significantly during the swing phase of gait (p=0.021) post-intervention together with a significant increase in the peak knee flexion angle during swing (p=0.038). The concentric group showed significant differences between pre and post-rehabilitation in knee flexion range of movement during the swing phase of gait (p=0.030). Significant correlations between knee joint stiffness and the quadriceps:hamstring co-activation ratio were observed in the concentric intervention group pre-intervention: during the pre-activation phase of gait between knee joint stiffness and vastus medialis / biceps femoris (r=-0.68; p=0.042) and during load acceptance phase of gait between knee joint stiffness and vastus lateralis / biceps femoris (r=0.07; p=0.036). The eccentric group recorded neuromuscular changes post-intervention with a significant decrease in the muscle activity of the biceps femoris during load acceptance phase of gait (p=0.021). The eccentric group had significantly better functional outcomes in the overall score of Knee injury and Osteoarthritis Outcome post-intervention (p=0.008) with a significant increase in function seen in the Sports and Recreation subgroup (p=0.008) and a significant increase in the level of activity as measure by the Tegner Activity Scale post-intervention (p=0.028), despite not showing any significant changes in the knee joint kinetics and kinematics. The concentric group only reported a significant increase in the overall score of the of the SF-36 Health Survey (p=0.011) with significant increases in three of the subgroups post-intervention: Bodily pains had improved (p=0.042), the role limitations due to physical heath had improved (p=0.028) and the role limitations due to emotional health had also improved (p=0.009). The concentric group also showed significant improvement in the emotional health over the intervention in comparison to the eccentric intervention group (p=0.020). Both intervention groups reported a similar significant increase in the distance covered during the six-minute walk test post-intervention (p=0.038). Conclusion: The results of this exploratory study did not find the eccentric cycling rehabilitation intervention exclusively more effective than the concentric cycling intervention in the restoration of functional ability in patients post-TKA. The eccentric intervention did however result in neuromuscular adaptations consistent with a move towards a more typical asymptomatic gait pattern and participants reported greater functional improvements on validated knee functional assessments and levels of activity scores. The concentric intervention yielded kinematic changes and participants reported improvements in their emotional and physical health post-intervention. Eccentric training and its role in early stage post-operative rehabilitation is limited. Based on the findings from this exploratory study, the benefit of eccentric training as an adjunct to rehabilitation and its role in contributing to greater improvements in the restoration of functional ability post-TKA needs to be further explored.